Day of the iguana - Winkler, Henry, 1945- (New York : Grosset & Dunlap, 2003)
Hank has never been fond of his sister's pet iguana and then the iguana lays eggs inside the cable box which was going to be Hank's science project, which causes many problems for Hank.
"The world's greatest underachiever."
670
Accelerated Reader AR
Keywords: Pets -- Fiction; Brothers and sisters -- Fiction; Iguanas -- Fiction; Humorous stories